Surface tension sound in superfluid helium films adsorbed on alumina powder - Rosenbaum, Ralph; Williams, G. A.; Heckerman, David; Marcus, J.; Scholler, D.; Maynard, J.; Rudnick, I. (Journal of Low Temperature Physics, 1979)
Sound propagation has been studied in He II films adsorbed on alumina powder grains (Al2O3). Sound velocity and adsorption isotherm data provide evidence that surf ace tension forces can exceed the van der Waals forces as the film thickness increases. A model of capillary condensation at the points where the powder grains touch accounts for many of the qualitative features of the data. The surface tension sound velocity decreases with increasing powder grain size.